Analisis dan Perancangan E-Learning Sebagai Fasilitas Pendukung Proses Pembelajaran (Studi Kasus: SMAK Kalam Kudus Ii ) - Agus Putranto; Idris Gautama; Daniel Citra (Bina Nusantara University, 2010)
Information and technology nowadays develop rapidly in every sector, including in education. Saome problem occurs in studying process, so that needed a system which is able to produce an E-Learning aplication that can be used to support the studying process at SMAK Kalam Kudus II. This observation try to analyze and design an E-Learning aplication at SMAK Kalam Kudus II. The final result is an E-Learning aplication that can be used to support the studying process at SMAK Kalam Kudus II between teachers ad students and also a facility such as lesson’s schedule, test’ schedule, download lessons and tasks, score and a media like forum that can link between parents and teachers.